Customer Attitudes towards A Public Sector Telecom Company (Bsnl) In Land Line (International Journal of Scientific Research and Management (IJSRM), 2016)
Customer attitudes are a composite of the three elements: cognitive information, affective information and information concerning a consumer’s past behavior and future intentions. In other words attitude consist of thoughts or beliefs, feelings and behaviors or intensions towards a particular thing which case is usually a good (concrete item) or service. Customers’ attitudes are highly important and evitable for the smooth functioning of an organization having public dealing and responsibilities. It depends on several factors like tangibility, reliability, assurance, superior service quality, empathy etc. This paper studied the various aspects of customer attitudes especially satisfaction, causes, reason, its impacts in telecom sector with suggestions. It is the main goal of every organization. Satisfaction level is a function of difference between perceived performance and expectations. If the products’ performance exceed expectation the customer highly satisfied or delighted. If the performance matches the expectation the customer is satisfied and if the product performance fall shorts of expectation the customer is dissatisfied. In the present scenario, the telecommunication is life blood for every business activities. It depends on several factors like tangibility, reliability, assurenc, superior service quality etc.